2004
DOI: 10.1128/jvi.78.6.3099-3109.2004
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Nef Protein Targets CD4+T Cells for Apoptosis by Interacting with CXCR4 Surface Receptors

Abstract: The effects of soluble Nef protein on CD4؉ T cells were examined. CD4 ؉ -T-cell cultures exposed to soluble Nef were analyzed for apoptosis by terminal deoxynucleotidyltransferase-mediated dUTP-biotin nick end labeling and hallmarks of apoptosis including cytoplasmic shrinkage, nuclear fragmentation, DNA laddering, and caspase activation. We observed dose-and time-dependent inductions of apoptosis. DNA laddering and activated caspase 3 were also evident. Cells treated with Nef/protein kinase inhibitor complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
95
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(100 citation statements)
references
References 68 publications
4
95
1
Order By: Relevance
“…In human monocyte-derived macrophages (MDMs), Nef activates the STAT1 pathway and the secretion of MIP-1, IL-1-α, IL-6, and TNF-α [102]. Extracellular Nef found in HIV patients (approximately 10 ng/ml) enters the vascular endothelium in vivo via CXCR4 [103]. Finally, Nef can be proapoptotic or prosurvival, depending on the context of expression and the particular cell type [104].…”
Section: Pathobiologymentioning
confidence: 99%
“…In human monocyte-derived macrophages (MDMs), Nef activates the STAT1 pathway and the secretion of MIP-1, IL-1-α, IL-6, and TNF-α [102]. Extracellular Nef found in HIV patients (approximately 10 ng/ml) enters the vascular endothelium in vivo via CXCR4 [103]. Finally, Nef can be proapoptotic or prosurvival, depending on the context of expression and the particular cell type [104].…”
Section: Pathobiologymentioning
confidence: 99%
“…19,20 We have also shown that cellfree tissue culture supernatant contains Nef, which can also induce apoptosis in T cells. To confirm the apoptotic activity of the microvesicular Nef isolated in this study we exposed Jurkat and U937 cells to Nef-GFP microvesicles for 3, 6, or 18 h (Fig.…”
Section: Nef Microvesicles Induce Apoptosis In Jurkat T-lymphocytes Bmentioning
confidence: 99%
“…[16][17][18] More specifically, early reports demonstrate that soluble extracellular Nef induces apoptosis in T cells via a CXCR4-dependent interaction. 19,20 Given this result, we have considered whether soluble Nef is released from infected cells and could play a significant role in mediating bystander apoptosis in CD4 þ T cells. Nef has no known intrinsic enzymatic activities and yet it promotes pleiotropic effects such as enhancement of infectivity, immune evasion, and cellular activation.…”
Section: Introductionmentioning
confidence: 99%
“…Although rare, PH complicating HIV infection has not decreased appreciably with available antiretroviral therapy (ART), and the mechanistic link between PH and HIV has not been clearly established (4). Although HIV ribonucleic acid (RNA) has not been isolated in the pulmonary vasculature, HIV proteins such as Tat and Nef cause endothelial dysfunction (6)(7)(8)(9)(10)(11)(12). It stands to reason that other viral infections may cause downstream fibroproliferation and remodeling in the pulmonary circulation.…”
mentioning
confidence: 99%